2020
DOI: 10.3389/fmats.2020.572955
|View full text |Cite
|
Sign up to set email alerts
|

A Case Study of Industrial Symbiosis to Reduce GHG Emissions: Performance Analysis and LCA of Asphalt Concretes Made With RAP Aggregates and Steel Slags

Abstract: The concept of sustainability in the road construction sector is a complex issue because of the various steps that contribute to the production and release of greenhouse gas (GHG) emissions. Addressing this issue, the European Commission has put various policy initiatives in place to encourage the construction industry to adopt circular economy (CE) and industrial symbiosis (IS) principles e.g., the use of recycled materials. Cooperativa Trasporti Imola (CTI), a company located in the Emilia-Romagna region (It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…In particular, the impact indicators IR, OFT and MR of CMRA RAPJGW are on average 12% lower than those of CMRA RAP due to the lower gaseous and particulate air emissions and minerals consumption required to produce the aggregates and cement (see Table 2b). The same results have been demonstrated by Bonoli et al [81], who showed that the recycling of RAP combined with steel slag aggregates provides benefits by reducing the consumption of virgin bitumen and aggregates and, at the same time, by reducing the CO 2 equivalent emissions.…”
Section: Lca Indicatorssupporting
confidence: 80%
“…In particular, the impact indicators IR, OFT and MR of CMRA RAPJGW are on average 12% lower than those of CMRA RAP due to the lower gaseous and particulate air emissions and minerals consumption required to produce the aggregates and cement (see Table 2b). The same results have been demonstrated by Bonoli et al [81], who showed that the recycling of RAP combined with steel slag aggregates provides benefits by reducing the consumption of virgin bitumen and aggregates and, at the same time, by reducing the CO 2 equivalent emissions.…”
Section: Lca Indicatorssupporting
confidence: 80%
“…Several steps contribute to the production of GHG, but the material extraction and production stage has been identified as the main contributor to total carbon emissions and energy consumption [12]. Hence, the choice of materials impacts local pollution and environmental degradation [13].…”
Section: Introductionmentioning
confidence: 99%
“…The bottleneck is the difficulty of demonstrating the condition for by-products relating to the certainty of use (condition a) under the Waste Framework directive (WFD) article 5). In this context, industrial symbiosis initiatives at regional or national level, supported by a planning actions using MFA, will allow establish industrial symbiosis network among various companies in the road construction and rehabilitation sector [ 59 ] to achieve sustainable commercial opportunities for its members and to use resources efficiently.
Fig.
…”
Section: Resultsmentioning
confidence: 99%